Report from the First Meeting of the Pedagogical Research Methodology Team at the KNP PAN - Pasikowski, Sławomir; Rubacha, Krzysztof (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
Report from the inaugural meeting of the Pedagogical Research Methodology Team (ZMBP) at the KNP PAN, which took place on 17 of May in 2017, at the Faculty of Pedagogical Sciences of the Nicolaus Copernicus University in Toruń.